The firm location race – Regulating incentive packages given to firms by local and regional governments - Philip Hanke; Hanke Philip; Heine Klaus (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes the competition between jurisdictions for the relocation of firms and its implications for the various national and international subsidy control regimes (state aid control). We model the attraction of firms to jurisdictions through subsidies as a race with continuous investment over time, where local governments exert inefficiently high efforts, which increase with the number of competitors and their respective spending. This setting makes the case for better investment and subsidy controls by higher-level governments while emphasizing structural problems of implementation at the same time.
Keywords: H71; K21; L50; 330